Can we create filters to clean dirty water?. (July 2018) - Ahmed, Sabiriin; Anderson, Anthony; Barreiro, Kevin; Benkhenniche, Yasmin; Brown, Lily-Rose; Dwamena-Chambers, Taejaun; Dykes, Hannah; Feliz, Carla-Maria; Giegiel, Klaudia; Grabowski, Aleksander; Houghton, Eleanor; Hristozov, Nedyalko; et al.
We wanted to find out if we could create filters to filter dirty water. We learnt about billions of people not having access to clean water all over the world. We wrote clear instructions explaining what we should do. This was also if anyone wanted to repeat this experiment. We organised which materials and methods we were going to use. We made detailed observations and wrote down the end results.